1996
DOI: 10.1128/jvi.70.6.4017-4027.1996
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for the TAR element in promoting efficient human immunodeficiency virus type 1 reverse transcription

Abstract: The regulation of human immunodeficiency virus type 1 (HIV-1) gene expression is dependent on the transactivator protein Tat and an RNA element extending from the transcription initiation site to ؉57 known as TAR. TAR forms a stable RNA secondary structure which is critical for high levels of HIV-1 gene expression and efficient viral replication. Using a genetic approach, we isolated HIV-1 mutants in TAR that were competent for high levels of gene expression but yet were markedly defective for viral replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 60 publications
2
46
2
1
Order By: Relevance
“…It has recently been suggested that destabilization of the TAR hairpin reduces the reverse transcription efficiency (27). In our study, destabilization of the 5Ј poly(A) hairpin also resulted in reduced reverse transcription, but we demonstrate that this defect is primarily the result of a reduction in the genomic RNA content of the mutant virions.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…It has recently been suggested that destabilization of the TAR hairpin reduces the reverse transcription efficiency (27). In our study, destabilization of the 5Ј poly(A) hairpin also resulted in reduced reverse transcription, but we demonstrate that this defect is primarily the result of a reduction in the genomic RNA content of the mutant virions.…”
Section: Discussioncontrasting
confidence: 43%
“…There is now substantial evidence that the R region of HIV-1 RNA molecules contains two critical hairpin structures. Previous studies demonstrated the importance of the TAR stem-loop structure in viral replication (26,27,34,46). In this study, we focused on the adjacent structure, the poly(A) hairpin ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intact TAR element is also critical for the regulation of reverse transcription of the HIV-1 genome [39]. It was interesting to investigate whether Tat was also involved in regulating this process.…”
Section: Tat As Hiv-1 Transcription Factormentioning
confidence: 99%
“…Precisely how these RNA interactions function in RTN is not known, but RNA stem-loop structures are associated with pausing by RT and by RNA polymerase II during synthesis [14,[18][19][20], which makes it somewhat surprising that mutations in the A-rich loop which prevent kissing-loop base pairing result in decreased initiation efficiency and reduced virus replication kinetics [17]. Likewise, subtle changes in RNA sequences upstream of the PBS inhibit proviral DNA synthesis [21][22][23][24][25], but the precise role of these sequences in RTN is also unknown.…”
Section: Introductionmentioning
confidence: 99%